2018
DOI: 10.1002/ccd.27906
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of impaired hepato‐renal function assessed by the MELD‐XI score in patients undergoing percutaneous mitral valve repair

Abstract: Objectives The objective of this study was to assess the prognostic value of the Model for End‐stage Liver Disease (MELD)‐XI score in patients undergoing PMVR with the MitraClip system. Background MELD‐XI score, which was originally developed for prognostic assessment in patients with advanced liver disease, has been reported as a predictor of outcome in heart failure patients. Methods A total of 192 consecutive patients undergoing percutaneous mitral valve repair (PMVR) were included into final analysis. MELD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
15
1
1
Order By: Relevance
“…To our best knowledge, our study demonstrated to the first time in the medical literature that MELD-XI score can be used as a predictor of in-hospital mortality among patients with CRT-D or ICD that presented with either decompensated heart failure or device shock or electrical storm. While previous studies have reported that MELD-XI score may predict both short and long-term prognosis in various patient populations (13)(14)(15)22,23,25,26), we demonstrated that it significantly predicted in-hospital mortality. We demonstrated that a cut-off value of ≥ 13.88 for MELD-XI score was associated with a significant risk of in-hospital mortality with a relatively fair sensitivity and specificity.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…To our best knowledge, our study demonstrated to the first time in the medical literature that MELD-XI score can be used as a predictor of in-hospital mortality among patients with CRT-D or ICD that presented with either decompensated heart failure or device shock or electrical storm. While previous studies have reported that MELD-XI score may predict both short and long-term prognosis in various patient populations (13)(14)(15)22,23,25,26), we demonstrated that it significantly predicted in-hospital mortality. We demonstrated that a cut-off value of ≥ 13.88 for MELD-XI score was associated with a significant risk of in-hospital mortality with a relatively fair sensitivity and specificity.…”
Section: Discussioncontrasting
confidence: 75%
“…Toplamda 16 (%15,1) hasta hastanede öldü. Hastanede ölen hastaların ortanca MELD-XI skoru yaşayanlardan anlamlı şekilde daha yüksekti (11,80 (0,59-28,98)'e karşılık 15,24 (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)64); p<0,05). İkili lojistik regresyon analizinde MELD-XI skorunun hastane içi mortalitenin bağımsız öngördürücüsü olduğu gösterildi (X 2 =1,229 (%95 CI 1,06-1,43); p<0,05).…”
unclassified
“…In addition, the predictive value of the MELD-XI score for the composite outcome within 2 years after TMVR was greater than those of eGFR and total bilirubin, separately. The optimal cut-off value of the MELD-XI score is different in various populations of HF [5,7,8,21,22]. We used one of the cut-off values previously reported and found a similar validity of the cut-off value in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the MELD-XI score is reported as a risk-stratification tool in patients with valvular interventions [20,21]. In patients undergoing TMVR, Spieker et al previously reported the association between the MELD-XI score and all-cause mortality during one-year follow-up in a single-center population [22]. In the present study, we validated the use of this score on a multicenter large-scale cohort of TMVR patients, and additionally assessed the impact of MELD-XI score on the incidence of HF hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also focused on the role of liver dysfunction in various clinical scenarios. Thus the role of cholestasis was evaluated in acute decompensated heart failure 21 and high as well as increasing MELD displayed worse outcome in patients after surgery for infective endocarditis 22 . Moreover, MELD independently predicted mortality rates in patients undergoing cardiac surgery 23 or implantation of left ventricular assist devices 24 .…”
Section: Discussionmentioning
confidence: 99%